1999
DOI: 10.1016/s0891-5245(99)90093-7
|View full text |Cite
|
Sign up to set email alerts
|

Newborn hypoglycemia

Abstract: Neonatal hypoglycemia is a common problem encountered by both term and preterm infants. It can be either symptomatic or asymptomatic. Prolonged hypoglycemia may result in permanent neurologic impairment and death. Definitions of hypoglycemia vary and remain controversial. Underlying causes of hypoglycemia include (a) inadequate glucose production; (b) increased glucose utilization; (c) abnormalities of endocrine regulation; and (d) other causes. Nurse practitioners must be aware of infants at risk for hypoglyc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 3 publications
0
10
1
Order By: Relevance
“…Although a number of risk factors and signs and symptoms are often noted in the literature as occurring with hypoglycemia (Armentrout & Caple, 1999;Eidelman, 2001;Rozanace & Hay, 2006;Sunehag & Haymond, 2002;WHO, 1997), this study found that only 6 of 23 common screening factors were positive in more than 7 of the 220 subjects in our study (maternal diabetes history, GA < 38 weeks, large for gestational age (LGA) or small for gestational age (SGA) size, hypothermia, jitteriness, and tachypnea). Only two of those screening factors were found to be statistically associated with the infant's PBG values: infant jitteriness and tachypnea.…”
Section: Absent In Subjectscontrasting
confidence: 56%
See 3 more Smart Citations
“…Although a number of risk factors and signs and symptoms are often noted in the literature as occurring with hypoglycemia (Armentrout & Caple, 1999;Eidelman, 2001;Rozanace & Hay, 2006;Sunehag & Haymond, 2002;WHO, 1997), this study found that only 6 of 23 common screening factors were positive in more than 7 of the 220 subjects in our study (maternal diabetes history, GA < 38 weeks, large for gestational age (LGA) or small for gestational age (SGA) size, hypothermia, jitteriness, and tachypnea). Only two of those screening factors were found to be statistically associated with the infant's PBG values: infant jitteriness and tachypnea.…”
Section: Absent In Subjectscontrasting
confidence: 56%
“…The incidence of hypoglycemia is highest in newborn infants of diabetic, preeclamptic, and/or substance abusing mothers, and in infants with low or high birthweight for their gestational age (GA), hypoxemia, cyanosis, hypothermia, and/or those born early (Alkalay et al, 2006;Armentrout & Caple, 1999;Eidelman, 2001;Sunehag & Haymond, 2002;WHO, 1997).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Infants constitute another group at risk of hypoglycemia, which can be related to conditions such as inadequate glucose production, increased glucose utilization, and abnormal regulation of metabolism (Armentrout and Caple, 1999;Hawdon, 1999;Sperling and Menon, 1999;Glaser, 2000;Ozand, 2000). Neonatal hypoglycemia can also be the result of failure to adapt from the fetal state of continuous glucose supply through the placenta to the extrauterine state involving intermittent nutrient supply.…”
Section: Introductionmentioning
confidence: 99%